(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background: Pituitary adenoma, which accounts for 17.4% of all brain tumors, is the third most frequently diagnosed brain tumor, following intracranial glioma and meningioma. The visual disturbance in pituitary adenoma ranged from blurring of vision with or without headache to total loss of vision. In patients with visual field defects, bitemporal hemianopia was the commonest visual field defect. Early improvement of visual function is one of the major indication surgery. Objective: The purpose of this study was to comparison between the pre and post-operative visual parameters and to find out the value in assessment of the prognosis of early postoperative visual function and also to find out the factor which influence the early post-operative visual outcome. Methods: A prospective study was done from September 2010 to April 2012 in the department of neurosurgery, Bangabandhu Sheikh Mujib Medical University, 30 cases of pituitary adenoma had been included in this study of those who were presented with visual symptoms. Visual assessment was done before the operation and outcome was analyzed at discharged from hospital. Results: Within 60 eyes, 13 (43.3%) patients presented with blindness of one or both eyes. 10 (33.3%) presented with uniocular and 3 (10.0%) presented with binocular blindness. Duration of the symptoms ranged from 2 months to 48 months. Patients underwent either transcranial or transsphenoidal tumor decompression. At discharge out of 30 patients, 23 (76.7%) showed improvement, 2 (6.6%) patients were deteriorated post-operatively. P value was <0.001, in z test, Z=91.5, which was highly significant. Post-operative visual status was analyzed with age, sex, duration of symptoms, suprasellar extension, and methods of surgery and extent of tumor resection to find out that any other factor influenced the visual outcome. In bivariate analysis it was shown that only duration of the symptoms only other factor that influenced the visual outcome (statistically significant, p value 0.017). Conclusion: With this study it was statistically proved that pre-operative visual status is the main factor for improvement of early post-operative visual outcome in pituitary adenoma and duration of symptoms had also influence the early post-operative visual outcome. Duration less than 12 months had a favorable outcome. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17182 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 108-115